Digitalisasi dan Pengembangan Administrasi Sekolah di Yayasan Perintis Pendidik Nusa - Mujahidah, Atika (TSAQOFAH, 2025)
School administration digitalization is an essential solution to enhance the efficiency and quality of educational management in the modern era. Yayasan Perintis Pendidik Nusa faces challenges in managing administration manually, which is often inefficient and prone to errors. This study aims to evaluate the effectiveness of the program using descriptive qualitative and quantitative approaches. Data were collected through observations,structured interviews, surveys, and documentation. The results indicate that implementing digital administration successfully improved efficiency and accuracy in data management, such as student records, attendance, and document numbering.